Analysis of symbolic number comparison tasks in terms of numerical stroop and distance effect - Mutlu, Yılmaz; Olkun, Sinan (Sakarya University, 2017)
The purpose of this study is to examine symbolic number comparison tasks in terms of stroop and distance effect. Participants in the study consisted of 313 third grade students, 157 girls and 156 boys, randomly selected from 17 different primary schools from two cities located in different regions of Turkey. The symbolic number comparison test used as data collection tool in the study contains 36 items. The test was designed according to stroop and distance effec and administered on a tablet computer. Data were analysed in terms of 1, 2, 3 distance and congruent, incongruent and neutral cases between the pairs of numbers. The results show that correlation between accuracy of incongruent items and the total correct number response is highest (.929) and there aremeaningful differences between all variables in term of accuracy and response time. The Stroop and distance effects were also confirmed by the results. © The Turkish Online Journal of Educational Technology.
Keywords: Distance effect; Dyscalculia; Number comparison task; Stroop effect